Effect of Fermentation Duration of Arabica Coffee through the Wine Process on the Physical and Organoleptic Quality of Coffee Powder - Heni Parida; Syahirman Hakim; Irwansyah; Nuraida (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2026)
Coffee is one of the agricultural commodities that has a very high economic value. Coffee beans are generally processed in several ways, namely the wet method, one of the stages of processing coffee beans that greatly determines quality is the fermentation method. The purpose of this study was to determine the physical characteristics of coffee powder and the organoleptic quality of coffee powder during fermentation. The parameters observed in this study were the water content of coffee powder, color, aroma, bitterness, and texture. The results showed that the fermentation time of 25 days affected the water content of coffee beans, which was 11.33%. From the results of organoleptic tests on coffee quality, it showed a significant effect on the color, aroma and texture of coffee powder. Panelists preferred the coffee powder brew in the 25 day fermentation treatment. Keywords: Fermentation, Powder arabica coffee, water content, color and texture